Peran Kepala Sekolah Sebagai Motivator Kinerja Guru di SMP Islam Al Azhar 29 BSB Semarang - Muhammad Rizal; Syaiful Bakhri (STAI Terpadu Yogyakarta, 2023)
Motivation is important because it affects how productive you are at work. Effective school leaders can boost teacher morale and productivity through mentoring and encouragement. This study investigates how the role of the principal affects teacher performance. The research method uses qualitative descriptive. Data collection using interview, observation, and recording techniques. Data analysis using data reduction techniques. The results showed that the role of the principal as a motivator of teacher performance at SMP Islam Al Azhar 29 BSB Semarang has been quite good. The headmaster strives to improve teacher performance in planning (with reference to IMTAQ). The Principal has performed his duties as a motivator of teacher performance well which includes: managing the physical environment, regulating the work atmosphere, instilling discipline, giving rewards, providing encouragement and providing learning resources through the learning resource center.